PENGARUH IKLAN DAN KEPERCAYAAN MEREK TERHADAP NIAT BELI KONSUMEN INTERNET 4G PLUS INDOSAT OOREDOO DI KOTA SURABAYA - HASUDUNGAN SIHOMBING, DANDY (Jurnal Ilmu Manajemen (JIM), 2016)
Indosat Ooredoo launched a new product called Internet 4G Plus as the fastest internet up to 185 Mbps at an affordable price. 4G plus IM3 Ooredoo offers many bonuses of data, digital content and also telephone. This study aims to analyze and discuss the influence of advertising and brand trust terhadapniat consumer buying. The population in this study are all people who do not use the internet connection in addition to 4G Plus Indosat Ooredoo. In this study, researchers used 165 samples. Methods of data collection in this study is the observation, documentation and questionnaires. The sampling method is particularly nonprobability sampling using purposive sampling. Measuring instrument used is multiple linear regression. The results show that partial advertising influence on purchase intention and brand trust influenced the purchase intention. Keywords: advertising, brand trust, purchase intentions.